The influence of workload and work-life balance on employee job satisfaction at PT. Ichiko Agro Lestari, Terentang District - Ahmad Riyadho; M Irfani Hendri (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to analyze the influence of workload and work-life balance on employee job satisfaction at PT Ichiko Agro Lestari in Terentang District. The background of the study is based on the characteristics of the agribusiness sector which demands high work intensity, uncertain working hours, and limited time flexibility that have the potential to affect employee well-being. The research method used is a quantitative approach with a causal design. Data were collected through a Likert-scale questionnaire distributed to all 34 employees (total sampling). Data analysis was carried out using validity and reliability tests, as well as multiple linear regression with the help of Statistical Package for the Social Sciences (SPSS) version 25 software. The results showed that workload had a positive and significant effect on employee job satisfaction, while work-life balance did not show a significant effect partially. However, both variables simultaneously proved to have a significant effect on job satisfaction with a coefficient of determination of 41.8%. This finding indicates that proportional workload management plays an important role in increasing job satisfaction, while the implementation of work-life balance still requires more adaptive policy support.